Mapping B-cell responses to Salmonella enterica serovars Typhimurium and Enteritidis in chickens for the discrimination of infected from vaccinated animals - Naqid, Ibrahim A.; Owen, Jonathan P.; Maddison, Ben C.; Spiliotopoulos, Anastasios; Emes, Richard D.; Warry, Andrew; Flynn, Robin J.; Martelli, Francesca; Gosling, Rebecca J.; Davies, Robert H.; La Ragione, Roberto M.; Gough, Kevin C. (Nature Publishing Group, 2016)
Serological surveillance and vaccination are important strategies for controlling infectious diseases of food production animals. However, the compatibility of these strategies is limited by a lack of assays capable of di erentiating infected from vaccinated animals (DIVA tests) for established killed or attenuated vaccines. Here, we used next generation phage-display (NGPD) and a 2-proportion Z score analysis to identify peptides that were preferentially bound by IgY from chickens infected with Salmonella Typhimurium or S. Enteritidis compared to IgY from vaccinates, for both an attenuated and an inactivated commercial vaccine. Peptides that were highly enriched against IgY from at least 4 out of 10 infected chickens were selected: 18 and 12 peptides for the killed and attenuated vaccines, respectively. The ten most discriminatory peptides for each vaccine were identi ed in an ELISA using a training set of IgY samples. These peptides were then used in multi-peptide assays that, when analysing a wider set of samples from infected and vaccinated animals, diagnosed infection with 100% sensitivity and speci city. The data describes a method for the development of DIVA assays for conventional attenuated and killed vaccines.